1996
DOI: 10.1046/j.1365-313x.1996.09020195.x
|View full text |Cite
|
Sign up to set email alerts
|

Tissue‐specific expression of Arabidopsis AKT1 gene is consistent with a role in K+ nutrition

Abstract: AKT1, a putative inwardly directed K+ channel of Arabidopsis, restores long-term potassium uptake in a yeast mutant defective in K+ absorption. In this paper, the expression pattern of the gene encoding AKT1 is described. Northern blots indicate that AKT1 transcripts are preferentially accumulated in Arabidopsis roots. Owing to the difficulties in producing large quantities of Arabidopsis roots under hydroponic conditions, experiments were undertaken with Brassica napus, a related species. Potassium starvation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
263
0
4

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 336 publications
(282 citation statements)
references
References 0 publications
15
263
0
4
Order By: Relevance
“…How-Yi Wang et al 827 npg ever, little is known about the regulatory mechanism of these K + transporters. AKT1 has been identified as an important dual-affinity inward-rectifying K + channel participating in K + uptake from soil into cells in Arabidopsis roots [9][10][11][12]. More recently, we have demonstrated that AKT1 activity is positively regulated by a protein kinase AtCIPK23, and AtCIPK23 is in turn activated by AtCBL1 or AtCBL9 [13].…”
Section: Introductionmentioning
confidence: 94%
“…How-Yi Wang et al 827 npg ever, little is known about the regulatory mechanism of these K + transporters. AKT1 has been identified as an important dual-affinity inward-rectifying K + channel participating in K + uptake from soil into cells in Arabidopsis roots [9][10][11][12]. More recently, we have demonstrated that AKT1 activity is positively regulated by a protein kinase AtCIPK23, and AtCIPK23 is in turn activated by AtCBL1 or AtCBL9 [13].…”
Section: Introductionmentioning
confidence: 94%
“…Thus, KATZ is predominantly expressed in guard cells (Nakamura et al, 1995) and AKTZ is predominantly expressed in the epidermis, cortex, and endodermis of the mature root, and also in hyadothodes (Cao et al, 1995;Lagarde et al, 1996). KSTZ, the potato K A T l homolog, is also expressed in guard cells and flowers, indicating the conservation of tissue-specific expression in different species (Miiller-Rober et al, 1995).…”
Section: P-domainmentioning
confidence: 99%
“…For the GUS assay, plants were either cultivated in vitro under the same conditions or grown in soil mixed with vermiculite in a greenhouse under continuous light at 228C. GUS histochemical staining was performed according to Lagarde et al (1996).…”
Section: Cloning Of Complementation and Gus Expression Constructs: Exmentioning
confidence: 99%